2012
DOI: 10.1037/a0026363
|View full text |Cite
|
Sign up to set email alerts
|

Performance on Delay Tasks in Early Childhood Predicted Socioemotional and School Adjustment Nine Years Later: A Longitudinal Study in Chinese Children

Abstract: This study examined, in a sample of Chinese children, the relations between early childhood delay behavior and later socioemotional and school adjustment. Observational data on delay behavior based on two delay tasks were collected when the children were two years old. Follow-up data on social competence, distinguished studentship, learning problems, perceived self-worth, loneliness, and depression were collected in the sample ( N = 175) from multiple sources, including teacher and mother ratings, self-reports… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…Results from previous studies have demonstrated that self‐control is negatively associated with internalizing problems in Chinese children (e.g., Chen, Zhang, et al, ). However, interactions among these variables over time had yet to be explored.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Results from previous studies have demonstrated that self‐control is negatively associated with internalizing problems in Chinese children (e.g., Chen, Zhang, et al, ). However, interactions among these variables over time had yet to be explored.…”
Section: Discussionmentioning
confidence: 90%
“…At the behavioral level, self‐control is typically defined as the ability to comply with a request, delay an action on request, and to behave according to social expectations (Kopp, ). The ability to intentionally control behavior to achieve specific goals helps children concentrate in school, cope with negative experiences such as distress and frustration, and behave appropriately in social situations (Chen, Zhang, Chen, & Li, ; Eisenberg et al, ). Indeed, self‐control can be viewed as a component of social competence, as it facilitates appropriate social behavior and is associated with receiving positive social evaluations from others (Mintz, Hamre, & Hatfield, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…References to characters' emotions might also differ across ethnicities. Influenced by the value of self-expression in an individualistic culture, European American mothers tend to use language to express personal opinions and feelings, whereas Chinese mothers value the restraint of emotion and desires and thus are reluctant to talk directly about emotions (Chen, Zhang, Chen, & Li, 2012;Chen et al, 1998;Doan & Wang, 2010;Wang et al, 2000). Chinese mothers are less likely than European American mothers to refer to thoughts and emotions during book-sharing (Doan & Wang, 2010;Wang et al, 2000).…”
Section: Contentmentioning
confidence: 99%